FERMI/LAT OBSERVATIONS OF LS 5039 - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Axelsson, Magnus; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; et al. (Astrophysical Journal Letters, 2009)
The first results from observations of the high-mass X-ray binary LS 5039 using the Fermi Gamma-ray Space Telescope data between 2008 August and 2009 June are presented. Our results indicate variability that is consistent with the binary period, with the emission being modulated with a period of 3.903 +/- 0.005 days; the first detection of this modulation at GeV energies. The light curve is characterized by a broad peak around superior conjunction in agreement with inverse Compton scattering models. The spectrum is represented by a power law with an exponential cutoff, yielding an overall flux ( 100 MeV-300 GeV) of 4.9 +/- 0.5(stat) +/- 1.8(syst) x 10(-7) photon cm(-2) s(-1), with a cutoff at 2.1 +/- 0.3(stat) +/- 1.1(syst) GeV and photon index G = 1.9 +/- 0.1(stat) +/- 0.3(syst). The spectrum is observed to vary with orbital phase, specifically between inferior and superior conjunction. We suggest that the presence of a cutoff in the spectrum may be indicative of magnetospheric emission similar to the emission seen in many pulsars by Fermi.
CRIS-Team WoS Importer:2020-01-15